1983
DOI: 10.1111/j.1471-6402.1983.tb00835.x
|View full text |Cite
|
Sign up to set email alerts
|

Gender Typing and Social Desirability of Personality in Person Evaluation

Abstract: In order to test the hypothesis that persons with gender-appropriate, as compared with gender-inappropriate, traits are evaluated more favorably, a person perception task was designed. Subjects ( n = 21 1) rated written descriptions of males and females who were said to possess either masculine or feminine personality characteristics, which, in turn, were either socially desirable or undesirable. Contrary to hypothesis, gender appropriateness had no significant effects on evaluation. Instead, ratings were stro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1984
1984
2002
2002

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Masculine individuals of both sexes were more positively evaluated on some dimensions while feminine individuals of both sexes received higher ratings on others. Stoppard and Kalin (1983) also found no evidence of sex bias but strong effects of sex-typing of personality characteristics assigned to stimulus persons. They had subjects make ratings of male and female stimulus persons, described in masculine or feminine terms (controlled for social desirability), in the areas of adjustment, interpersonal functioning, academic competence and likelihood of achieving future success.…”
Section: Apparent Absence Of Sex Biasmentioning
confidence: 74%
See 1 more Smart Citation
“…Masculine individuals of both sexes were more positively evaluated on some dimensions while feminine individuals of both sexes received higher ratings on others. Stoppard and Kalin (1983) also found no evidence of sex bias but strong effects of sex-typing of personality characteristics assigned to stimulus persons. They had subjects make ratings of male and female stimulus persons, described in masculine or feminine terms (controlled for social desirability), in the areas of adjustment, interpersonal functioning, academic competence and likelihood of achieving future success.…”
Section: Apparent Absence Of Sex Biasmentioning
confidence: 74%
“…According to role theory, it would then follow that individuals having out-of-role characteristics should be devalued in contrast to persons with role appropriate traits. Several studies reviewed in this paper have obtained results not in line with this prediction, in that there was no negative reaction towards persons showing out-of-role characteristics (Dipboye & Wiley, 1977,1978Harris, 1977;Kalin, Battle & Heusser, in press;Stoppard & Kalin, 1983). In all these studies, information about the personality characteristics of stimulus persons was available to raters.…”
Section: N -I I Assertive Figurementioning
confidence: 84%
“…In addition to scholastic standing and qualifications, the attribution of personality characteristics to stimulus persons also seems to influence judgements about them. Studies by Harris (1976Harris ( , 1977 and Stoppard and Kalin (1983) found that masculine stimulus persons (both males and females) received higher ratings on some dimensions, and feminine persons on others, but that no sex bias characterized the judgements. These results suggest that the sex congruency model may be limited to situations where raters have little or no relevant information for their judgements.…”
mentioning
confidence: 96%
“…Qualitative approaches were mentioned only in passing, if at all. As a doctoral student, I employed conventional experimental methods and statistical modes of analysis in the research conducted for my dissertation on gender stereotypes (Stoppard & Kalin, 1978, 1983). When I became an academic psychologist in the late 1970s, I found myself in a department in which the predominant methodology was quantitative-experimental, something that has not changed a great deal in the intervening years.…”
Section: Setting the Scene: Becoming A Qualitative Researchermentioning
confidence: 99%